Analysis of the Physical Integrity of Earth Dams from Electrical Resistivity Tomography (ERT) in Brazil - Camarero, Pedro Lemos; Moreira, César Augusto [UNESP]; Pereira, Henrique Garcia (Springer Nature, 2019)
Dams are structures that barrier rivers and streams for a variety of purposes. The constant maintenance of these structures is essential, since a possible accident can lead to damage of catastrophic proportions. In November 2015 in the city of Mariana, Minas Gerais (MG), Brazil, a tailings dam burst and spilled 56 million cubic meters of tailings. In addition to victimize 19 people, the event caused material, economic and environmental damage—it is considered the largest environmental disaster of Brazil. This research presents a cheap and quickly applied alternative for investigation of seepage of water in earth dams, built with distinct embankment materials—one dam composed of predominantly silt and clay soil and the other predominantly composed of sandy soil. The research methods used were: geotechnical tests as gradation test, permeability test with the Guelph permeameter method and the application of the (DC) resistivity geophysical method from the electrical resistivity tomography (ERT) technique in Wenner array. Three ERT lines were positioned parallel to the longitudinal axis at each dam. The data are presented in 2D and 3D geophysical images with electrical resistivity values modeled. Based on the physical principle of electrolytic conduction, i.e., decrease in electrical resistance in materials or siliceous minerals in moisture conditions compared to the material in the dry state, the results revealed low-resistivity zones restricted to some points, associated with water infiltration in the transverse direction. The results indicate saturation restricted to some points and low permeability, at the present time, an installation of piping processes.
Keywords: dams; electrical resistivity; geophysics; Internal erosion; tailings